Family Conversations About Heat and Temperature: Implications for Children’s Learning - Luce, Megan R.; Callanan, Maureen A. (Frontiers in Psychology, 2020)
Some science educators claim that children enter science classrooms with a conception of heat considered by physicists to be incorrect, and speculate that “misconceptions” may result from the way heat is talked about in everyday language (e.g., Lautrey & Mazens, 2004; Slotta & Chi, 2006). We investigated talk about heat in naturalistic conversation to explore the claim that children often hear heat discussed as a substance rather than a process, potentially hindering later learning of heat as energy involved in emergent processes. We explored naturalistic speech among children and adults to understand the nature and frequency of heat- and temperature-related conversations that young children are involved in. This study aims to investigate the actual linguistic resources that children have available, as part of a sociocultural approach to cognitive development. Parents’ everyday conversations about heat and temperature with their 2- to 6-year-old children were drawn from the CHILDES language database and from a parent-child book-reading study. Parents used the word heat rarely, but did so in ways that implied it is a substance. Parents never talked about heat as an emergent process, but sometimes as a direct causal process. Most of the heat- and temperature-related talk, however, focused on words like hot and cold to describe temperature as a property of objects. This investigation of what young children actually experience in everyday conversations is a step toward studying how everyday language may play a role in children’s understanding of heat and temperature.